ESTUDIO SOBRE EL LLAMADO EPITELIO ESTRATIFICADO DEL ESOFAGO DE RANA PIPIENS SCHREBER - BRICENO CASTREJON, B (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
The lethal dose of k-strophanthoside was detd in 40 cats subjected to muscular work by the continuous stimulation of both sciatic nerves The avg lethal dose for these animals was significantly greater than that detd under identical conditions in 40 ca
AN ESC NAC CIENC BIOL
Keywords: ESTUDIO, EPITELIO, ESTRATIFICADO, ESOFAGO, RANA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL (ZOOLOGIA); FISIOLOGIA ANIMAL